Implementasi Teknologi IoT dalam Sistem Pemantauan Kualitas Udara di Politeknik Negeri Bengkalis - Kurniawaty, Eva; Muhamad Nasir; M.Khairul (Buletin Ilmiah Informatika Teknologi, 2024)
The campus environment, with its high daily activity, has the potential to cause air pollution if not managed properly. Therefore, it is crucial to monitor and maintain air quality at Politeknik Negeri Bengkalis to ensure a safe and healthy environment for the entire academic community. This research aims to design and implement an Internet of Things (IoT)-based air quality monitoring system that provides real-time information about air quality to users. The system utilizes MQ-2 and MQ-135 sensors to detect levels of carbon monoxide (CO) and carbon dioxide (CO2), with programming following specific protocols. The primary focus of this research is to develop a monitoring device that measures CO and CO2 levels and promotes efforts to improve air quality. Testing of the system was conducted at Politeknik Negeri Bengkalis, and the results indicated that the average CO levels fall within the normal or good category, and CO2 levels are also considered good. This research is expected to contribute to efforts to maintain air quality on campus, supporting the health and safety of the entire academic community. Keywords: Campus, Pollutan, Internet of Things, CO, CO2.